Formulation and evaluation of pectin-hydroxypropyl methylcellulose coated curcumin pellets for colon delivery - Sureshkumar, R; Munikumar, Munikumar; Ganesh, G N K; Jawahar, N; Nagasamyvenkatesh, D; Senthil, V; Raju, L; Samantha, M K (Asian Journal of Pharmaceutics (AJP), 2014)
High molecular weight hydroxypropyl methylcellulose (HPMC) and biodegradable pectin were used for coating the pellets containing curcumin, to be released in the colon. The prepared pellets were freeflowing. in vitro release of curcumin remained intact up to pH 3.0, disintegrated at pH 7.2, and released up to 12 hours. The ideal batch (1:3) showed minimum release at pH 1.2 and maximum release at pH 6.8, and an increased amount of curcumin in the blood stream(1.287 Î¼g/ml) was achieved when compared with pure curcumin (0.5 Î¼g/ml). The drug release was retarded by the high concentrationand greater thickness of the coating of HPMC on the pellets. Release kinetics of the preparation shows a non-Fickian or anamolous diffusion or matrix erosion.